USING C # IN DESIGNING HUMAN-MACHINE INTERFACE - Драпак, Лариса Семенівна (Eastern-European Journal of Enterprise Technologies, 2012)
The use of the language C # and Visual Studio.NET programming environment for creating (design and construction) of man-machine interface is considered. Specified on the effectiveness of such use, including the construction of various types of graphics is indicated.